Fenomena Photo Dump di Media Sosial pada Mahasiswa Universitas Al-Qolam Malang - Rima Mufida; Nurul Azizah (Universitas Islam Negeri Madura, 2025)
The Trend of photo dump story templates has recently emerged as a distinct phenomenon on Instagram, with many users, especially those from Generation Z, actively engaging in it. According to Albert Bandura's Social Cognitive Theory, individuals learn behaviors through observation of their environment, including content on social media. This study aims to analyze the photo dump template trend through Bandura’s perspective among Gen Z adolescents, using a qualitative method with a descriptive approach and data analyzed through Miles and Huberman’s interactive model. The results show that this phenomenon occurs through three main stages: observation, where users view others’ Instagram stories and are cognitively influenced to imitate them; modeling, where they replicate the trend by editing and uploading personal photos without concerns of plagiarism; and self-efficacy, where users gain confidence from the freedom to express themselves without the pressure of appearing aesthetically perfect. From Bandura’s viewpoint, this trend represents a form of social learning that has become a new cultural and social norm on Instagram, where blurry, candid, or visually plain photos are increasingly appreciated for their authenticity. For Gen Z, photo dumps offer a way to express their lives honestly, resist excessive validation, and avoid the social pressure to maintain an idealized online persona.